Stroke Iskemik pada Pasien Hemodialisis : Laporan Kasus - Thiodorus, Fira; Mayung, Claraiva; Yuliani, Desie (Fakultas Kedokteran Universitas Trisakti, 2023)
Stroke and chronic kidney disease are major health problems worldwide. Acute ischemic stroke is a significant complication in patients with end-stage renal disease undergoing hemodialysis. The incidence of stroke is about 8-10 times higher in chronic renal failure patients on hemodialysis compared to the general population. The annual incidence rate of acute ischemic stroke is reported to be about 4% in chronic renal failure patients on hemodialysis. Initiation of dialysis in chronic renal failure patients is associated with an increased risk of stroke. Chronic renal failure disease is an independent risk factor for stroke. A 57-year-old woman complained of left-side weakness during hemodialysis. Paresis of cranial nerve VII and XII and grade 3 flaccid hemiparesis sinistra were found. Electrocardiogram showed normal atrial fibrillation response. Non-contrast head CT scan showed subacute ischemic cerebral infarction in the right internal capsule. Factors that cause stroke in chronic renal failure are endothelial dysfunction, accelerated arteriosclerosis, and impaired cerebral autoregulation.